Effects of dalteparin on anti‐Xa activities cannot be predicted in critically ill COVID‐19 patients. Issue 6 (17th January 2022) - van der Heijden, Charlotte D. C. C.; ter Heine, Rob; Kooistra, Emma J.; Brüggemann, Roger J.; Walburgh Schmidt, Jesper W. J.; de Grouw, Elke P. L. M.; Frenzel, Tim; Pickkers, Peter; Leentjens, Jenneke
Abstract : Critically ill COVID‐19 patients are at high risk of thromboembolic events despite routine‐dosed low‐molecular‐weight heparin thromboprophylaxis. However, in recent randomized trials increased‐intensity thromboprophylaxis seemed futile and possibly even harmful. In this explorative pharmacokinetic (PK) study we measured anti‐Xa activities on frequent timepoints in 15 critically ill COVID‐19 patients receiving dalteparin and performed PK analysis by nonlinear mixed‐effect modelling. A linear one‐compartment model with first‐order kinetics provided a good fit. However, wide interindividual variation in dalteparin absorption (variance 78%) and clearance (variance 34%) was observed, unexplained by routine clinical covariates. Using the final PK model for Monte Carlo simulations, we predicted increased‐intensity dalteparin to result in anti‐Xa activities well over prophylactic targets (0.2‐0.4 IU/mL) in the majority of patients. Therapeutic‐intensity dalteparin results in supratherapeutic anti‐Xa levels (target 0.6‐1.0 IU/mL) in 19% of patients and subtherapeutic levels in 22%. Therefore, anti‐Xa measurements should guide high‐intensity dalteparin in critically ill COVID‐19 patients.